The Koshkonong Creek Village Site (47je0379): Ceramic Production, Function, and Deposition at an Oneota Occupation in Southeastern Wisconsin - (:unkn) unknown (My University, 2018)
The ceramic assemblage recovered from excavations at the Koshkonong Creek Village (KCV) site (47JE0379) is examined to determine functional and stylistic significance from a temporal and spatial perspective. Occupied from circa A.D. 1000 to 4000, KCV presents an opportunity to look at Oneota in the locality from its early to late iterations. The ceramics were analyzed by attributes and categorized in a type-variety system laid out by Schneider (2015) for comparative purposes. Using a household approach and a feature-level analysis, ceramics trends are mapped and explored using GIS. The research collected lends credence to noted trends of cultural continuity in the locality, as well as some differences to be explored with future research. Results have implications for housing structures, the temporal use of ceramics, and shared ideology in the Koshkonong locality. While individual features and the excavated material recovered from each feature were not able to be directly tied to specific housing structures, the data still informs on domestic activity that occurred during the daily life of the Oneota household at KCV. Comparisons are made to other local sites, including Carcajou Point (47JE0002), Schmeling (47JE0833), and Crescent Bay Hunt Club (47JE0904).
Keywords: Ceramics; Oneota